Study Of Social Harmony Construction Between Hindu And Muslim Society - Halim, Abdul; Kesuma, Arsyad Sobby (Opción, 2019)
The aim of the study is to investigate social harmony construction between Hindu and Muslim society. Mixed methodology, a combination of qualitative and quantitative methods in a form of case study, including collecting, analyzing, and integrating data, in a single or gradual study, was applied to collect accurate, comprehensive, and objective data. As a result, all parties, especially the elite, should act and think synergistically in facing the diversity that exists in Indonesia. In conclusion, harmony between Hindus and Muslims is supported by the presence of Nyawa Braya applied in daily activities, including religious and social activities.